Embracing virtuality: User acceptance of virtual settings for learning. (July 2021) - Carrion, Belinda; Gonzalez-Delgado, Carlos A; Mendez-Reguera, Aniela; Erana-Rojas, Irma Elisa; Lopez, Mildred
Highlights: Virtuality allow participants to feel present in a computer-generated environment. These environments need an atmosphere of enjoyment, ease of use, and emotional immersion. Virtual settings promote exciting and unexpected immersive adventures. Educational institutions are investing in VR and AR as a complement to students' training. Abstract: Immersion in virtual settings allows participants to perceive, understand, and feel present in a computer-generated environment. User experience in a virtual setting is highly dependent on the fidelity of represented objects and surroundings, and the degree of interaction it provides. Understanding the users' perception and acceptance of virtual settings is a priority to predict the potential of its incorporation in the curriculum. An instrument was applied to 85 university students measuring ease of use, enjoyment, and emotional immersion on a 1 to 7 Likert scale where 7 represents the highest score. The ease of use acceptance achieved a mean of 6.61, enjoyment 7, and emotional immersion 6.81. The results emphasize that users were enthusiastic and participative; these positive emotions reassure the high potential of virtuality in educational settings. Graphical abstract: Image, graphical abstract